FvHsfB1a Gene Improves Thermotolerance in Transgenic Arabidopsis - Qian Cao; Tingting Mao; Kebang Yang; Hanxiu Xie; Shan Li; Hao Xue (Plants)
Heat stress transcription factor (Hsf) families play important roles in abiotic stress responses. However, previous studies reported that HsfBs genes may play diverse roles in response to heat stress. Here, we conducted functional analysis on a woodland strawberry Class B Hsf gene, FvHsfB1a, to improve thermotolerance. The structure of FvHsfB1a contains a typical Hsf domain for DNA binding at the N-terminus, and FvHsfB1a belongs to the B1 family of Hsfs. The FvHsfB1a protein was localized in the nucleus. The FvHsfB1a gene was expressed in various strawberry tissues and highly induced by heat treatment. Under heat stress conditions, ectopic expression of FvHsfB1a in Arabidopsis improves thermotolerance, with higher germination and survival rates, a longer primary root length, higher proline and chlorophyll contents, lower malonaldehyde (MDA) and O2− contents, better enzyme activities, and greater expression of heat-responsive and stress-related genes compared to WT. FvWRKY75 activates the promoter of the FvHsfB1a gene through recognizing the W-box element. Similarly, FvWRKY75-OE lines also displayed a heat-tolerant phenotype, exhibiting more proline and chlorophyll contents, lower MDA and O2− contents, and higher enzyme activities under heat stress. Taken together, our study indicates that FvHsfB1a is a positive regulator of heat stress.